PERLINDUNGAN HUKUM KONSUMEN ATAS KESAMAAN BUNYI MEREK TERHADAP BARANG YANG TIDAK SEJENIS - Evelyn Larissa Florentia Wijaya (STIH Putri Maharaja, 2020)
The practical purpose of the article is to find out whether consumers get legal protection if something goes wrong in choosing a product that has similar terms but different classification of types. The research is juridical-normative. With regard to the case of MICROCIDE (pharmaceutical preparations) and MICROZID (disinfectant), abviously the isues are different from trademark infringement in general. The use of different terminologies will possible to make consumers to be wrong in choosing the products which can cause a danger when it is consumed. There is remain legal vacuum in the absence of implementing regulations that regulate the same brand in principle for goods that are not of the same type so that consumer’ rights cannot be fulfilled.